ANALYSIS OF THE DATA FROM THE SIUCE PLATAFORM 2020-2023 ON TEENAGE PREGNANCY IN COLOMBIA - Sandra Milena Arizmendi; Erika Johanna Ballesteros Moreno (LÍNEA IMAGINARIA, 2025)
The National System of School Coexistence (SIUCE) originated from Law 1620 of 2013, aimed at identifying, registering, and monitoring cases of various issues, including teenage pregnancy within the school environment. This study reviews aspects of teenage pregnancy to observe trends, determine vulnerable populations, and provide a contextual reading of educational institutions across the country. One of its objectives is to prevent school dropout due to teenage pregnancy and motherhood. For this purpose, a documentary analysis of the 2023 Report was conducted, which does not present the total data of 992 cases for that year alone, but rather the 2,146 cases reported from 2020 to 2023, along with the UNFPA report for Latin America and the Caribbean. It is important to note that pregnancy cases involving girls under 14 years old are considered crimes in Colombia, making the analysis of the mothers’ ages relevant, with the highest prevalence of teenage pregnancy occurring at age 16. Additionally, the 10th and 11th grades show the highest number of pregnancy cases. Unfortunately, there is a lack of detailed information regarding the fathers. This analysis provides a contextual understanding that could guide future promotion and prevention activities aimed at student support, life planning, sexual education, and citizenship building, in line with Law 2383 of July 2024.